Discovery and characterisation of sweetpotato's closest tetraploid relative - Data files - Munoz Rodriguez, P; Scotland, R W; Wells, T; Wood, J R I; Anglin, N L; Jarret, R L (University of Oxford, 2021)
The data deposited here is associated with a scientific paper. The data include phylogenies (Newick format), DNA alignment files (Fasta format), morphological dataset (TXT format), Principal Component Analysis files, reference files (Fasta, Fai and Dict formats) and scripts (Bash and R languages). The abstract of that paper is: